(untitled) (BIRDEM Medical Journal, 2017)
Wilsons disease is an inherited disorder in which defective biliary excretion of copper leads to its accumulation, particularly in liver and brain. Presentation can vary, but the key features of Wilsons disease are hepatic and neuropsychiatric disturbances, KayserFleischer rings of the cornea, acute episodes of hemolysis and sometimes renal impairment. Here, we report a case of Wilsons disease in a young female having severe anaemia without other evidence of hepatic and neuropsychiatric manifestation. Birdem Med J 2017; 7(3): 233-234